INTERNATIONAL FIELD PRACTICE (PPL): PROBLEMS, IMPLEMENTATION, AND COMMUNITY RESPONSES - Andang Saehu; Hani Hartiani Putri; Dewi Putri Nabila; Irman Nurhapitudin (Pusat Pengabdian kepada Masyarakat LP2M UIN Sunan Gunung Djati Bandung, 2019)
Abstrak This paper is an evaluative study to explore and analyze the process of implementing the International PPL, the problems encountered in the implementation of International PPL, and the community responses to the implementation of International PPL. In working with the implementation, International PPL was conducted in three steps: pre-field research activities, whilst field research activities, and post-field research activities. Some internal and external problems faced in the implementation of this International PPL. The responses to the International PPL implementation were gained from both internal and external communities.